SUPPORT VECTOR MACHINES UNTUK MENYELESAIKAN MASALAH KLASIFIKASI PADA PENGENALAN POLA - Abdul Azis Abdillah (Politeknik Negeri Jakarta, 2019)
ABSTRACTSupport Vector Machines (SVM) are known as the latest machine learning (machine learning) methods to solve classification problems in pattern recognition. This paper discusses the use of SVM in solving problems in pattern recognition. An example of the problem given in this paper contains a collection of data on Any Linearly Separable Datase, Any dataset with Noise, and Real datasets.Key words: machine learning, pattern recognition, SVMABSTRAKSupport Vector Machines (SVM) dikenal sebagai metode machine learning (pembelajaran mesin) paling mutakhir untuk menyelesaikan masalah klasifikasi pada pengenalan pola. Tulisan ini bertujuan untuk membahas penggunaan SVM dalam memecahkan masalah klasifikasi pada pengenalan pola. Contoh masalah yang diberikan pada tulisan ini meliputi klasifikasi data pada Sembarang Linearly Separable Dataset, Sembarang Dataset dengan Noise, dan Real dataset.Kata kunci : klasifikasi, pengenalan pola, SVM